Validation of the pathological narcissistic inventory (PNI) and its brief form (B-PNI) in the Arabic language - Diana Malaeb; A. Esin Asan; Feten Fekih-Romdhane; Vanessa Azzi; Abir Sarray El Dine; Souheil Hallit; Aaron L. Pincus (BMC Psychiatry, 2023)
Abstract Background The Pathological Narcissism Inventory (PNI) is a multidimensional measure developed to assess narcissistic grandiosity and narcissistic vulnerability. We aimed to validate the Arabic version of the original Pathological Narcissistic Inventory (PNI) and its brief form (B-PNI) in a community sample of Lebanese adults. Methods The English language PNI items were translated into Arabic following a rigorous translation, back-translation, and linguistic evaluation. A total of 401 participants were administered the translated PNI, as well as previously validated Arabic versions of the Big Five Inventory-2, the Rosenberg Self-esteem Scale, the Patient Health Questionnaire (PHQ-9), and the Impulsivity-8 Scale. Results Exploratory and confirmatory analyses supported the existence of seven first-order and two second-order factors of the PNI and B-PNI. Except for exploitativeness where females scored lower than males, no other significant differences by gender were observed for the remaining PNI subscale scores. Additionally, scores on all the subscales exhibited good reliability, while the associations with external measures supported the concurrent validity of the translated instrument. Conclusion The results of this study suggest that scores on the PNI and B-PNI are highly reliable with satisfactory concurrent and factorial validity, providing an assessment of broadly defined pathological narcissism among the Lebanese young adult population. The availability of the Arabic PNI and its brief form should facilitate improved understanding of pathological narcissism in Arabic cultures and the different factors that govern narcissistic personality pathology.